An Analysis of Social Values in the Silent Child Film and Its Relevance to Characteristics of a Teacher’s Social Competence - Rufaida Muslimah; Dini Hidayati; Lenny Solo (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
Today the presence of mass media has a great influence on society. One of the mass media that provides a function in providing entertainment to the public is film. Film is one of the communication media in conveying a message to a group of people that is audio-visual. This study aims to find out the social values contained in the film The Silent Child and to find out the relevance of social values in the film The Silent Child with the characteristics of a teacher's social competence. The approach used in this study is a qualitative approach. This research method is descriptive and included in library research, because the main source of data for this research is the silent child film. The data collection technique in this study was by means of observation, namely observing and watching every scene of the film The Silent Child carefully. The results of this study are social values of affection, namely family, loyalty, care, and there are social values of responsibility, namely possession, discipline and empathy in the film The Silent Child. The relevance of the social values in the silent child film with the characteristics of a person's social competence, namely first, empathy and polite communication, second, knowledge of human relationships, and third, mastering social psychology.